The Effect of Word of Mouth Marketıng on the Purchase Behavıor Vıa Brand Image and Perceıved Qualıty - Zuhrem Yaman (Montenegrin Journal of Economics)
In terms of businesses in today's world, the most important way of sustainability is through a good sense of quality and a brand image. Especially when the uncertainties about the service to be offered in the service sector are excessive, people can postpone the decision stage as long as they are not confident. For a service that they do not already have experience, the customers choose the way to prefer perceived quality perception and businesses with high brand image with the help of word of mouth marketing. In this study, it is aimed to determine whether word of mouth marketing has effect on the purchasing behavior via brand image and perceived quality. In order to collect the data in the study, scales which consists of 23 items, 89 for Cronbach Alpha internal consistency coefficient word of mouth marketing, 80 for brand image, 92 for perceived quality, developed by Goyette vd (2010), Ural and Perk (2012) and Pappu, Quester ve Cooksey (2006) was used. As a result of the analyzes made, it has been found out that word of mouth marketing activities develop faster on the institutions which had high percieved quality and brand image before, and on the purchasing behaviors of the individuals.